Molecular genetic and biochemical profiles of malignant neoplasms during pregnancy - A. L. Chernyshova; A. A. Chernyakov; Yu. M. Truschuk; N. V. Yunusova; N. V. Sevostyanova; Ya. I. Arkhipova; O. S. Dil; A. E. Chernyshova (Успехи молекулярной онкологии)
The article presents a review of modern literature data on molecular-genetic and biochemical profiles of malignant tumors of varying locations. It is shown that molecular-genetic and transcription profiles of pregnancy-associated malignant tumors are systems consisting of various components, many of which remain poorly researched. Additionally, morphological and biochemical characteristics of the placenta and tumor tissue are discussed. In the recent years, individual researchers and research groups have demonstrated heightened interests in this problem which undoubtedly soon will lead to a deeper and stronger understanding of mechanisms of progression and metastasis of oncological diseases during pregnancy. The knowledge of the principles of normal embryogenesis as a process of intrauterine development of a fetus, as well as investigation of molecular basis of pathogenesis of spontaneous abortion will undoubtedly help in determination of new targets and development of new therapeutical molecules for cancer treatment.